Field Marshal Sir Henry Wilson - Jeffery, Keith.
1 online resource (340 pages)
Keywords: Henry Wilson was at the centre of affairs during the First World War and after, recording everything in his wildly indiscreet diary. Using a range of official and private sources, this is the first modern biography of this controversial and misunderstood figure.